Politics, ideology and football fandom : the transformation of modern Poland - Kossakowski, Radosław (Routledge, 2020)
Football fans and their political engagement in Central and Eastern Europe -- Socio-economic and political transformation of Poland since the collapse of communism -- Football fandom in Poland in a historical perspective -- The pathological 1990s -- Polish political elites versus football fandom -- Contemporary Polish fandom and its civic, social and political engagement -- Ideology on Polish terraces -- Polish national team supporters -- Fans and politics : towards a typology. Conclusions.